Persahabatan dalam Perspektif Platonis: Sebuah Refleksi bagi Pemuda Kristiani - Tanto, Wignyo; Sabdono, Erastus; Daniel, Albertus; Takain, William; Erastus, Stephanie (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2024)
Young people who exist and interpret their relationships horizontally really need to understand the meaning of their relationships, of course, in their friendships. The fundamental problem is that young people prioritize reciprocity in their friendly relations rather than the value of